Novel therapeutic approach to slow down the inflammatory cascade in acute/subacute spinal cord injury: Early immune therapy with lipopolysaccharide enhanced neuroprotective effect of combinational therapy of granulocyte colony-stimulating factor and bone-marrow mesenchymal stem cell in spinal cord injury - Hashemizadeh, Shiva; Hosseindoost, Saereh; Omidi, Ameneh; Aminianfar, Hossein; Ebrahimi-Barough, Somayeh; Ai, Jafar; Arjmand, Babak; Hadjighassem, Mahmoudreza (Frontiers in Cellular Neuroscience, 2022)
Bone-marrow mesenchymal stem cell (BM-MSCs) has not yet proven any significant therapeutic efficacy in spinal cord injury (SCI) clinical trials, due to hostile microenvironment of injured spinal cord at acute phase. This study aims to modulate inflammatory milieu by lipopolysaccharide(LPS) and granulocyte colony stimulating factor (G-CSF) to improve BM-MSCs therapy. For this purpose, we determined the optimum injection time and sub-toxic dosage of LPS following T10 contusion injury. Medium-dose LPS administration may result in a local anti-inflammatory beneficial role, This regulatory role is associated with an increase in NF-200-positive cells ,significant tissue sparing, and improvement in functional recovery compared to the SCI control group. The second aim was to examine potential ability of LPS and LPS +G-CSF combination therapy to modulate the lesion site before BM-MSC (1×105 cells) intra-spinal injection. Our results demonstrated combination therapy increased potency to enhance anti-inflammatory response (IL-10,Arg-1) , decrease inflammatory marker (TNF-a and CD86) and caspase-3 compared to BM-MSC monotherapy. Histological analysis revealed that combination groups displayed better structural remodeling than BM-MSC monotherapy. In addition, BBB score show increase motor recovery in all treatment groups. Moreover, drug therapy shows faster recovery than BM-MSC monotherapy. Our results suggest that sub-toxic dose of LPS provides neuroprotection to SCI and can promote the beneficial effect of BM-MSC in SCI. These findings suggest that a combination of LPS or LPS+G-CSF prior BM-MSC transplantation is a promising approach for optimizing BM-MSC based strategies to treat SCI. However; because of the lack of some methodological limitations to examine survival rate and ultimate fate of transplanted BM-MSC followed by LPS administration in this study, further research needs to be done in this area. The presence of only one-time point for evaluating inflammatory response (1week) after SCI, can be considered as one of the limitation of this study. we believed that inclusion of additional time points would provide more information about the effect of our combination therapy on the microglia/macrophage polarization dynamic at injured spinal cord.